Eco-banana peel plastics / Faiezah Hashim … [et al.] - Hashim, Faiezah; Che Ismail, Nor Hafizah; Mohd Zaini, Nurul Aizan; Din, Siti Nor; Abdul Salim, Zainathul Akhmar Salim (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
The environmental issues caused by the disposal of plastic waste have sparked interest in the production of environmentally friendly polymers. Low density of polyethylene (LDPE) is increasingly being used for food packaging and non-food packaging due to outstanding properties, ease of processing and higher ultraviolet (UV) resistance. However, the inability of LDPE to decompose in nature is opposed to disintegration and degradation, which is a genuine environmental issue. The introduction of banana peel starch (BPS), which is natural, abundant, organic, and biodegradable, is a potential way to increase the susceptibility of LDPE to environmental degradation. Banana peels are a waste product ideal for producing bioplastics, accounting for 18.5% of starch sources. The effect of PE-g-MA as compatibilizer and various amount of banana peel starch towards the properties of LDPE/BPS were determined using Fourier Transform Infra-Red (FTIR), Tensile testing and differential scanning calorimetry (DSC). As confirmed by FTIR, there is interaction between PE-g-MA with the matrix, thus enhance the tensile and thermal properties of the films. Hence, it was suggested that development of sustainable plastic material, based on banana peel starch and LDPE, that is ideal for the replacement of single-use, petroleum based and persistent packaging.